Electronic and nuclear dynamics of doubly core-ionized and excited states: Vibrationally resolved photoelectron and Auger spectra of small molecules. (August 2015) - Oberli, S; Sisourat, N; Selles, P; Carniato, S
Synopsis: In this work we want to assess the influence of nuclear dynamics on the features of the double corehole photoelectron and Auger spectra of small isolated molecules by performing wave packet propagation on precomputed ab initio potential energy surfaces.